Weed Control and Crop Tolerance in Inzen Grain Sorghum with Zest Tank Mixtures - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2015)
Although preemergence applications of Cinch ATZ provided excellent green foxtail control, it did not provide commercially acceptable levels of Palmer amaranth or crabgrass control. All postemergence tank mixes of Zest raised the level of control achieved by the preemergence applications of Cinch ATZ to excellent levels for these species. With the exception of the Huskie tank mix, which provided excellent Palmer amaranth control, all other postemergence programs provided only adequate control of Palmer amaranth, crabgrass, or green foxtail. Weed pressure of these species was extreme. Under conditions of extreme weed pressure, a foundation treatment of Cinch ATZ followed by a postemergence application would be needed for commercially acceptable levels of weed control.
Keywords: weed science; weed control; shattercane; green foxtail; crabgrass; kochia; Palmer amaranth; Russian thistle; preemergence herbicide; postemergence herbicide; Inzen; grain sorghum; Zest; tank mix; crop tolerance; Cinch ATZ; Huskie; nonirrigated sorghum; nicosulfuron; Accent